(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2017)
Three alternative ways of innovation are identified in the article by constructing a structural and logic scheme: intraprenership, exoprenership, purchasing of innovations. The problem of a selecting of an effective way of the proposed alternatives is detected. Numeric criteria values that must be considered when making a decision are chosen. The method of analytic hierarchy process of Saaty is chosen for solving the multicriterial optimization problem, the scale of a relative importance of elements is built, as well as, a pairwise comparison and systematization of each level of the hierarchy. The analysis of all acceptable solutions is carried out, and a normalized matrix is built by a linear convolution of the criteria. As a result of calculations, the formula for the numerical comparison of alternatives with regard to the selected criteria is deduced.